Feasibility Study for Transitioning from Conventional Banking to Islamic Banking - Maskuroh, Nihayatul; Suganda, Asep Dadan; Akbar, Kurni (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This study examines the feasibility and strategic approach for transitioning the Faculty of Economics and Islamic Business (FEBI) at UIN Sultan Maulana Hasanuddin Banten from conventional to Islamic banking. The transformation aims to align institutional operations with Islamic economic principles and strengthen ideological consistency. A quantitative SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis integrated with the Analytic Network Process (ANP) was employed to prioritize strategic alternatives, using Super Decisions software. Data were collected through surveys, interviews, and document analysis involving faculty members, staff, and students. The Internal Factor Evaluation (IFE) score of 3.60 and the External Factor Evaluation (EFE) score of 2.68 position the faculty in Quadrant I of the SWOT matrix, indicating an aggressive strategy. Survey results show 56.5% of respondents consider the shift “fairly important” and 50.8% view it as a valuable educational opportunity. Recommended strategies emphasize leveraging strengths to seize opportunities, addressing weaknesses, and mitigating threats. The findings suggest that transitioning to Islamic banking is both feasible and strategically advantageous, offering practical implications for policy alignment and operational implementation in higher education institutions seeking Sharia-compliant transformation